Continuous-flow hydration–condensation reaction: Synthesis of α,β-unsaturated ketones from alkynes and aldehydes by using a heterogeneous solid acid catalyst - Rueping, Magnus; Bootwicha, Teerawut; Baars, Hannah; Sugiono, Erli (Beilstein Journal of Organic Chemistry, 2011)
A simple, practical and efficient continuous-flow hydration–condensation protocol was developed for the synthesis of α,β-unsaturated ketones starting from alkynes and aldehydes by employing a heterogeneous catalyst in a flow microwave. The procedure presents a straightforward and convenient access to valuable differently substituted chalcones and can be applied on multigram scale.
Keywords: chalcones; flow reactor; green chemistry; heterogeneous catalysis, microwave

(untitled) - Jas, G.; Kirschning, A. (Chem.–Eur. J., 2003)

(untitled) - Kikutani, Y.; Kitamori, T. (Macromol. Rapid Commun., 2004)

(untitled) - Kirschning, A.; Solodenko, W.; Mennecke, K. (Chem.–Eur. J., 2006)

(untitled) - Watts, P.; Haswell, S. J. (Chem. Soc. Rev., 2005)

(untitled) - Geyer, K.; Codée, J. D. C.; Seeberger, P. H. (Chem.–Eur. J., 2006)

(untitled) - Mason, B. P.; Price, K. E.; Steinbacher, J. L.; Bogdan, A. R.; McQuade, D. T. (Chem. Rev., 2007)

(untitled) - Ahmed-Omer, B.; Brandt, J. C.; Wirth, T. (Org. Biomol. Chem., 2007)

(untitled) - Wiles, C.; Watts, P. (Eur. J. Org. Chem., 2008)

(untitled) - Yoshida, J-i.; Nagaki, A.; Yamada, T. (Chem.–Eur. J., 2008)

(untitled) - Kirschning, A. (Beilstein J. Org. Chem., 2009)

(untitled) - Jähnisch, K.; Hessel, V.; Löwe, H.; Baerns, M. (Angew. Chem., Int. Ed., 2004)

(untitled) - Razzaq, T.; Kappe, C. O. (Chem.–Asian J., 2010)

(untitled) - Wegner, J.; Ceylan, S.; Kirschning, A. (Chem. Commun., 2011)

(untitled) - Hartman, R. L.; McMullen, J. P.; Jensen, K. F. (Angew. Chem., Int. Ed., 2011)

(untitled) - Yamada, Y. M. A.; Torii, K.; Uozumi, Y. (Beilstein J. Org. Chem., 2009)

(untitled) - Brandt, J. C.; Wirth, T. (Beilstein J. Org. Chem., 2009)

(untitled) - Rolland, J.; Cambeiro, X. C.; Rodríguez-Escrich, C.; Pericàs, M. A. (Beilstein J. Org. Chem., 2009)

(untitled) - Kunz, U.; Turek, T. (Beilstein J. Org. Chem., 2009)

(untitled) - Gutmann, B.; Glasnov, T. N.; Razzaq, T.; Goessler, W.; Roberge, D. M.; Kappe, C. O. (Beilstein J. Org. Chem., 2011)

(untitled) - Wiles, C.; Hammond, M. J.; Watts, P. (Beilstein J. Org. Chem., 2009)

(untitled) - Singh, S.; Köhler, J. M.; Schober, A.; Groß, G. A. (Beilstein J. Org. Chem., 2011)

(untitled) - Fukuyama, T.; Mukai, Y.; Ryu, I. (Beilstein J. Org. Chem., 2011)

(untitled) - Ley, S. V.; Baxendale, I. R. (Chimia, 2008)

(untitled) - Benito-López, F.; Egberink, R. J. M.; Reinhoudt, D. N.; Verboom, W. (Tetrahedron, 2008)

(untitled) - Bowman, M. D.; Holcomb, J. L.; Kormos, C. M.; Leadbeater, N. E.; Williams, V. A. (Org. Process Res. Dev., 2008)

(untitled) - Benali, O.; Deal, M.; Farrant, E.; Tapolczay, D.; Wheeler, R. (Org. Process Res. Dev., 2008)

(untitled) - Strauss, C. R. (Org. Process Res. Dev., 2009)

(untitled) - Styring, P.; Parracho, A. I. R. (Beilstein J. Org. Chem., 2009)

(untitled) - Bogdan, A.; McQuade, D. T. (Beilstein J. Org. Chem., 2009)

(untitled) - Mennecke, K.; Kirschning, A. (Beilstein J. Org. Chem., 2009)

(untitled) - Palmieri, A.; Ley, S. V.; Polyzos, A.; Ladlow, M.; Baxendale, I. R. (Beilstein J. Org. Chem., 2009)

(untitled) - Damm, M.; Glasnov, T. N.; Kappe, C. O. (Org. Process Res. Dev., 2010)

(untitled) - Lehmann, H.; LaVecchia, L. (Org. Process Res. Dev., 2010)

(untitled) - Lv, Y.; Yu, Z.; Su, W. (Org. Process Res. Dev., 2011)

(untitled) - He, P.; Haswell, S. J.; Fletcher, P. D. I.; Kelly, S. M.; Mansfield, A. (Beilstein J. Org. Chem., 2011)

(untitled) - Burguete, M. I.; García-Verdugo, E.; Luis, S. V. (Beilstein J. Org. Chem., 2011)

(untitled) - Schlange, A.; dos Santos, A. R.; Kunz, U.; Turek, T. (Beilstein J. Org. Chem., 2011)

(untitled) - Mak, X. Y.; Laurino, P.; Seeberger, P. H. (Beilstein J. Org. Chem., 2009)

(untitled) - Cambeiro, X. C.; Martín-Rapún, R.; Miranda, P. O.; Sayalero, S.; Alza, E.; Llanes, P.; Pericàs, M. A. (Beilstein J. Org. Chem., 2011)

(untitled) - Fritzsche, S.; Ohla, S.; Glaser, P.; Giera, D. S.; Sickert, M.; Schneider, C.; Belder, D. (Angew. Chem., Int. Ed., 2011)

Practical Microwave Synthesis for Organic Chemists - Kappe, C. O.; Dallinger, D.; Murphree, S. (Wiley-VCH, 2009)

(untitled) - Cablewski, T.; Faux, A. F.; Strauss, C. R. (J. Org. Chem., 1994)

(untitled) - Bagley, M. C.; Jenkins, R. L.; Lubinu, M. C.; Mason, C.; Wood, R. (J. Org. Chem., 2005)

(untitled) - Baxendale, I. R.; Pitts, M. R. (Chim. Oggi, 2006)

(untitled) - Shore, G.; Morin, S.; Organ, M. G. (Angew. Chem., Int. Ed., 2006)

(untitled) - Baxendale, I. R.; Griffiths-Jones, C. M.; Ley, S. V.; Tranmer, G. K. (Chem.–Eur. J., 2006)

(untitled) - Glasnov, T. N.; Kappe, C. O. (Macromol. Rapid Commun., 2007)

(untitled) - Baxendale, I. R.; Hayward, J. J.; Ley, S. V. (Comb. Chem. High Throughput Screening, 2007)

(untitled) - Shore, G.; Tsimerman, M.; Organ, M. G. (Beilstein J. Org. Chem., 2009)

(untitled) - Shore, G.; Yoo, W.-J.; Li, C.-J.; Organ, M. G. (Chem.–Eur. J., 2010)

(untitled) - Dressen, M. H. C. L.; van de Kruijs, B. H. P.; Meuldijk, J.; Vekemans, J. A. J. M.; Hulshof, L. A. (Org. Process Res. Dev., 2010)

(untitled) - Bagley, M. C.; Fusillo, V.; Jenkins, R. L.; Lubinu, M. C.; Mason, C. (Org. Biomol. Chem., 2010)

(untitled) - Rueping, M.; Bootwicha, T.; Sugiono, E. (Adv. Synth. Catal., 2010)

(untitled) - Wiles, C.; Watts, P. (Beilstein J. Org. Chem., 2011)

(untitled) - Won, S.-J.; Liu, C.-T.; Tsao, L.-T.; Weng, J.-R.; Ko, H.-H.; Wang, J.-P.; Lin, C.-N. (Eur. J. Med. Chem., 2005)

(untitled) - Trivedi, J. C.; Bariwal, J. B.; Upadhyay, K. D.; Naliapara, Y. T.; Joshi, S. K.; Pannecouque, C. C.; De Clercq, E.; Shah, A. K. (Tetrahedron Lett., 2007)

(untitled) - Nowakowska, Z. (Eur. J. Med. Chem., 2007)

(untitled) - Aponte, J. C.; Verástegui, M.; Málaga, E.; Zimic, M.; Quiliano, M.; Vaisberg, A. J.; Gilman, R. H.; Hammond, G. B. (J. Med. Chem., 2008)

(untitled) - Nowakowska, Z.; Kędzia, B.; Schroeder, G. (Eur. J. Med. Chem., 2008)

(untitled) - Bhattacharya, A.; Mishra, L. C.; Sharma, M.; Awasthi, S. K.; Bhasin, V. K. (Eur. J. Med. Chem., 2009)

(untitled) - Wang, S.; Yu, G.; Lu, J.; Xiao, K.; Hu, Y.; Hu, H. (Synthesis, 2003)

(untitled) - Bhat, B. A.; Dhar, K. L.; Puri, S. C.; Saxena, A. K.; Shanmugavel, M.; Qazi, G. N. (Bioorg. Med. Chem. Lett., 2005)

(untitled) - Schijlen, E. G. W. M.; de Vos, C. H. R.; Martens, S.; Jonker, H. H.; Rosin, F. M.; Molthoff, J. W.; Tikunov, Y. M.; Angenent, G. C.; van Tunen, A. J.; Bovy, A. G. (Plant Physiol., 2007)

(untitled) - Cabrera, M.; Simoens, M.; Falchi, G.; Lavaggi, M. L.; Piro, O. E.; Castellano, E. E.; Vidal, A.; Azqueta, A.; Monge, A.; de Ceráin, A. L.; Sagrera, G.; Seoane, G.; et al. (Bioorg. Med. Chem., 2007)

(untitled) - Siddiqui, Z. N.; Asad, M.; Praveen, S. (Med. Chem. Res., 2008)

(untitled) - Hayashi, A.; Yamaguchi, M.; Hirama, M. (Synlett, 1995)

(untitled) - Kokubo, K.; Matsumasa, K.; Miura, M.; Nomura, M. (J. Org. Chem., 1997)

(untitled) - Ishikawa, T.; Mizuta, T.; Hagiwara, K.; Aikawa, T.; Kudo, T.; Saito, S. (J. Org. Chem., 2003)

(untitled) - Curini, M.; Epifano, F.; Maltese, F.; Rosati, O. (Synlett, 2003)

(untitled) - Xu, L.-W.; Li, L.; Xia, C.-G.; Zhao, P.-Q. (Helv. Chim. Acta, 2004)

(untitled) - Viswanathan, G. S.; Li, C.-J. (Tetrahedron Lett., 2002)

(untitled) - Park, J. Y.; Ullapu, P. R.; Choo, H.; Lee, J. K.; Min, S.-J.; Pae, A. N.; Kim, Y.; Baek, D.-J.; Cho, Y. S. (Eur. J. Org. Chem., 2008)

(untitled) - Yadav, J. S.; Subba Reddy, B. V.; Vishnumurthy, P. (Tetrahedron Lett., 2008)

(untitled) - Jia, H.-P.; Dreyer, D. R.; Bielawski, C. W. (Adv. Synth. Catal., 2011)

(untitled) - Frantz, D. E.; Fässler, R.; Carreira, E. M. (J. Am. Chem. Soc., 2000)

(untitled) - Anand, N. K.; Carreira, E. M. (J. Am. Chem. Soc., 2001)

(untitled) - Gao, G.; Moore, D.; Xie, R.-G.; Pu, L. (Org. Lett., 2002)

(untitled) - Liu, Q.-Z.; Xie, N.-S.; Luo, Z.-B.; Cui, X.; Cun, L.-F.; Gong, L.-Z.; Mi, A.-Q.; Jiang, Y.-Z. (J. Org. Chem., 2003)

(untitled) - Trost, B. M.; Weiss, A. H.; Jacobi von Wangelin, A. (J. Am. Chem. Soc., 2006)

(untitled) - Scarpi, D.; Galbo, F. L.; Guarna, A. (Tetrahedron: Asymmetry, 2006)

(untitled) - Ramu, E.; Varala, R.; Sreelatha, N.; Adapa, S. R. (Tetrahedron Lett., 2007)

(untitled) - Yang, F.; Xi, P.; Yang, L.; Lan, J.; Xie, R.; You, J. (J. Org. Chem., 2007)

(untitled) - Krauzy-Dziedzic, K.; Ejfler, J.; Szafert, S.; Sobota, P. (Dalton Trans., 2008)

(untitled) - Xu, Z.; Mao, J.; Zhang, Y. (Org. Biomol. Chem., 2008)